PENGARUH MARKETING CAPABILITY TERHADAP CUSTOMER LOYALTY DENGAN CUSTOMER ENGAGEMENT DAN COMPETITIVE ADVANTAGE SEBAGAI VARIABEL INTERVENING PADA INDOSAT OOREDOO DI SURABAYA - Ervan Alexander Okhotan (Jurnal Strategi Pemasaran, 2015)
The development of communication media lead to an increase number of mobile device users in Indonesia, especially in Surabaya. This issue causes the telecommunication services become a major needs of the public so that Indosat Ooredoo face strong competition in winning the market. This research aims to analyze the effects of Marketing Capability  towards Customer Loyalty at Indosat Ooredoo in Surabaya with Customer Engagement  and Competitive Advantage as intervening variable. This research was conducted by distributing questionnaires to 100 respondents which are customer of Indosat Ooredoo. Quantitative analysis with path analysis model method were used for the techinal analysis.